2021
DOI: 10.3389/fonc.2021.638146
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Study on the Non-thermal Effects of Magnetic Field Therapy in Oncology

Abstract: Cancer is one of the most common causes of death worldwide. Although the existing therapies have made great progress and significantly improved the prognosis of patients, it is undeniable that these treatment measures still cause some serious side effects. In this context, a new treatment method is needed to address these shortcomings. In recent years, the magnetic fields have been proposed as a novel treatment method with the advantages of less side effects, high efficiency, wide applications, and low costs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 103 publications
(118 reference statements)
0
17
0
Order By: Relevance
“…Experiments on cells and cell cultures showed the effectiveness of NMMA as a means of inducing apoptosis in cancer cells [ 36 , 37 , 41 , 42 ]. In addition, there is indirect evidence of the possible participation of drugs containing iron ions, or natural iron-containing proteins-ferritins, in the mechanisms of MF action in vivo [ 138 , 139 , 140 , 141 ]. Of course, for a reliable proof of the magnetomechanical origin of the effects observed in vivo, it is necessary to conduct targeted experiments with the introduction of optimally designed MNPs, with known magnetic characteristics and functional shells, into the body, as well as physically substantiated parameters of the activating AMF.…”
Section: Some Experimental Resultsmentioning
confidence: 99%
“…Experiments on cells and cell cultures showed the effectiveness of NMMA as a means of inducing apoptosis in cancer cells [ 36 , 37 , 41 , 42 ]. In addition, there is indirect evidence of the possible participation of drugs containing iron ions, or natural iron-containing proteins-ferritins, in the mechanisms of MF action in vivo [ 138 , 139 , 140 , 141 ]. Of course, for a reliable proof of the magnetomechanical origin of the effects observed in vivo, it is necessary to conduct targeted experiments with the introduction of optimally designed MNPs, with known magnetic characteristics and functional shells, into the body, as well as physically substantiated parameters of the activating AMF.…”
Section: Some Experimental Resultsmentioning
confidence: 99%
“…14 ). There has been a developing body of evidence revealing that ELF-EMF has various effects on cellular processes and functions, including important signaling pathways e.g., apoptosis, autophagy, proliferation, differentiation, and cell cycle 45 . However, it is not clear how ELF-EMF affects cell response.…”
Section: Discussionmentioning
confidence: 99%
“…These differences could be related to the distinct effect of cell type on the variable expression of stress-related genes. Accumulating evidence shows that ELF-EMF can induce autophagy and show a potent anti-tumor effect 45 . Xu et al 60 showed that ELF-EMF induced autophagy causes cell death and suppresses lung cancer through up-regulating miR-486 expression and inhibit AKT/mTOR signaling.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed above, a vast variety of densities ranging from a few micro Tesla up to tens of milli tesla have been applied in studies examining effects of ELF‐EMF on apoptosis. 184 , 185 , 186 In addition, in some cases, promotion of apoptosis by ELF‐EMF exposure was examined in the presence of a co‐stressor (eg chemotherapeutic agents). One obvious result of these studies is that contrary to chemotherapeutic agents, ELF‐EMF exposure does not demonstrate a clear dose–response pattern.…”
Section: Anti‐/pro‐apoptotic Effects Of Elf‐emf: Statement Of the Controversymentioning
confidence: 99%